Sovereign wealth funds and cross-border investment bias: the case of Arab countries. Issue 1 (2nd January 2020) - Elbadawi, Ibrahim; Soto, Raimundo; Zaki, Chahir
ABSTRACT: Assets managed by sovereign wealth funds (SWF) have grown nine-fold since 2002, reaching USD 8 trillion in 2018. Around 80% of these investments correspond to cross-border investments. SWFs of Arab countries, mainly oil-rich GCC economies, hold a sizable fraction of these funds (40%). Asset allocation, nevertheless, presents a significant anomaly: despite the presence of highly endowed Arab-owned SWFs, cross-border investment in Arab economies is negligible in terms of transactions as well as of value. We study the allocation decisions of SWFs, both in terms of the probability of investing abroad (extensive margin) as well as the level of investment (intensive margin). In particular, we ask whether SWF investment decisions, at both margins, are largely determined by economic factors – e.g. profitability and risk – or are also influenced by strategic considerations, such as geopolitical interests. Our findings show that, while foreign investors have a positive bias for the Arab destination countries at the extensive margin level, there is a negative bias against them at the intensive one. At the sectoral level, results are highly heterogeneous as some sectors are sensitive to institutions (e.g. industry and consumer discretionary), while others are insensitive, such as energy.